Investigating the impact of adding new airline routes on air transportation resilience in China. (September 2022) - Wang, Xinglong; Peng, Jinhan; Tang, Junqing; Lu, Qiuchen; Li, Xiaowei
Abstract: When building new airports various strategies for initiating new air routes prominently affect the overall system performance. From a perspective of disruption management, however, very little is known regarding the impacts of different strategies exerted to the resilience of airline networks in a multi-layer system configuration. In this paper, we established a multi-layer China airline network (CAN) using route data from 46 airlines in mainland China and proposed four optimization strategies for adding new routes based on service-oriented perspectives. The geographical traits of the multi-layer CAN was first explored and, taking the Daxing International Airport (a new-built airport in Beijing, China) as a demonstrative example, we then conducted both qualitative and quantitative analyses to investigate the impact of the proposed strategies and their effectiveness of improving network resilience. It is revealed that those strategies have heterogeneous effects on the network performance in terms of meeting passenger demands and balancing overall connectivity at a national strategic level, and the overall resilience of the CAN could be significantly improved under the selected strategy by 59.8% on average. Based on the findings, several managerial and policy implications are put forward and discussed. This paper sheds new lights on resilience-building strategies for service carriers and airport managers and is also of value to regional governments for offering incentives for expanding connections to new destinations. Highlights: A comprehensive multi-layer airline network is constructed. The network consists of 46 layers of sub-networks from mainland China. Practical strategies are proposed and tested for improving network resilience. Optimized strategies improve the overall resilience of the multi-layer network by 59.8% on average. Implications for managing a growing multi-layer airline network are provided.